Perception of native vs. non-native language and non-speech sounds in one-week-old neonates: An fNIRS study - Yinchun Ma; Jianming Zhang; Ruochen Dang; Nan Wang; Yan Wang; Mei Yu; Mengmeng Chen; Peiting Shen; Quan Wang; Jinhua Huang (Brain Research Bulletin)
Background: Early infant phonological and non-phonological perceptual abilities are crucial for future language learning. Previous studies have focused on the changes in the cerebral cortex of infants and toddlers during speech perception, while the changes in the cerebral cortex during non-speech perception remain poorly understood. Objective: This study aimed to investigate cortical activation patterns and differences in full-term healthy newborns under different speech and non-speech stimuli by functional near-infrared spectroscopy (fNIRS). Methods: The cohort included 36 full-term healthy neonates (7.4 ± 6.0 days) exposed to two types of speech stimuli (native Mandarin and non-native Spanish) and three non-speech stimuli (music, cat calls, and noise) in a block design. Brain activity was monitored across eight brain regions of interest (ROIs) were monitored using fNIRS (54 channels): frontal pole area (FPA), middle frontal gyrus (MFG), primary sensorimotor cortex, middle temporal gyrus (MTG), superior temporal gyrus (STG), fusiform gyrus (FFG), Wernicke's area, and Broca's area. Results: Mandarin stimulation activated all ROIs in newborns. Changes in oxygenated hemoglobin concentrations in FPA, MFG, STG, MTG, FFG, Wernicke's area, and Broca's area were significantly higher during Mandarin exposure compared to Spanish (p < 0.05). MTG activation was significantly greater during Mandarin exposure compared to cat calls (p = 0.005), music (p = 0.040), and noise (p < 0.001). Similarly, MFG and Broca's area showed significantly greater activation during music exposure compared to Spanish and noise stimuli (p < 0.05). Conclusions: The newborn brain can perceive various speech and non-speech stimuli, demonstrating a preference for native language stimuli, followed by music. The ability to perceive non-native languages, animal calls, and noise appears more limited. These findings could provide some references for future research on infant and toddler language development.